Inhibition of neuroinflammation by GIBH-130 (AD-16) reduces neurodegeneration, motor deficits, and proinflammatory cytokines in a hemiparkinsonian model - Bianchetti, Maria E.; Ferreira, Ana Flavia F.; Britto, Luiz R. G. (Frontiers in Neuroanatomy, 2024)
Parkinson’s disease (PD) is a neurodegenerative condition characterized by the loss of dopaminergic neurons in the substantia nigra pars compacta (SNc) of the brain, manifesting itself with both motor and non-motor symptoms. A critical element of this pathology is neuroinflammation, which triggers a harmful neurotoxic cycle, exacerbating cell death within the central nervous system. AD-16 (also known as GIBH-130) is a recently identified compound capable of reducing the expression of pro-inflammatory cytokines while increasing the expression of anti-inflammatory cytokines in Alzheimer’s disease models. Here, for the first time, we sought to comprehend the potential impact of orally administered AD-16 in mitigating neurodegeneration and subsequent disease progression in PD. To accomplish this, 6- hydroxydopamine (6-OHDA) unilateral striatal injections were employed to induce a PD model in male C57BL/6 mice. Cylinder and apomorphine-induced rotation behavior tests were conducted to assess motor behavior and validate the PD model 3 days after the injection. AD-16 was administered via gavage daily between days 3 and 9 after surgery. On the last day of treatment, motor tests were performed again. All animals were euthanized on day 10 and immunohistochemistry techniques were performed to detect tyrosine hydroxylase (TH) and Iba-1 and thus label dopaminergic neurons and microglia in the SNc and striatum (CPu). These same regions were collected for ELISA assays to assess different cytokine concentrations. Our results revealed an enhancement in the motor function of the AD-16-treated animals, as well as reduced nigrostriatal neurodegeneration. In addition, AD-16 reduced the increase in microglia density and prevented the changes in its morphology observed in the PD animal models. Furthermore, AD-16 was able to avoid the increase of pro-inflammatory cytokines levels that were present in 6-OHDA-injected animals who received vehicle. Consequently, AD-16 emerges as a compound with significant potential for negative modulation of neurodegeneration and neuroinflammation suppression in the 6-OHDA animal model of Parkinson’s disease.